Transmigration of magnetite nanoparticles across the blood–brain barrier in a rodent model: influence of external and alternating magnetic fields. Issue 47 (21st November 2022) - Gupta, Ruby; Chauhan, Anjali; Kaur, Tashmeen; Kuanr, Bijoy K.; Sharma, Deepika
Abstract : Alternating magnetic field (AMF) and external magnetic field (EMF) mediated magnetic targeting-induced transport of magnetic nanoparticles (MNPs) across the blood brain barrier. Abstract : Despite advances in neurology, drug delivery to the central nervous system is considered a challenge due to the presence of the blood brain barrier (BBB). In this study, the role of magnetic hyperthermia induced by exposure of magnetic nanoparticles (MNPs) to an alternating magnetic field (AMF) in synergy with an external magnetic field (EMF) was investigated to transiently increase the permeability of the MNPs across the BBB. A dual magnetic targeting approach was employed by first dragging the MNPs by an EMF for an intended enhanced cellular association with the brain endothelial cells and then activating the MNPs by an AMF for the temporary disruption of the tight junctions of BBB. The efficacy of the BBB permeability for the MNPs under the influence of dual magnetic targeting was evaluated in vitro using transwell models developed by co-culturing murine brain endothelial cells with astrocytes, as well as in vivo in mouse models. The in vitro results revealed that the exposure to AMF transiently opened the tight junctions at the BBB, which, after 3 h of treatment, were observed to recover back to their comparable control levels. A biodistribution analysis of nanoparticles confirmed targeted accumulation of MNPs in the brain following dual targeting. This dual targeting approach was observed to open the tight junctions, thus increasing the transport of MNPs into the brain with higher specificity as compared to using EMF targeting alone, suggesting that a dual magnetic targeting-induced transport of MNPs across the BBB is an effective measure for delivery of therapeutics.